(untitled) (TAJ: Journal of Teachers Association, 2018)
Ulcerative colitis is an idiopathic inflammatory bowel disease characterized by continuous mucosal inflammation that starts in the rectum and extends proximally. Ulcerative colitis is considered frequent in majority of European and North American population and exceptional in most of the developing Asian countries. The present study was designed to estimate the disease severity and colonic involvement of ulcerative colitis in a tertiary care hospital of Rajshahi Medical College. The study population includes of 60 ulcerative colitis patients. Patients were categorized on the basis of disease severity ; moderate : 34, and severe: 26 and involvement of colon: 28 (46.40%) pancolitis, 20 (33.96%) left sided colitis and had 12 (19.61%) proctosigmoiditis. TAJ 2015; 28(2): 58-60